Women in the construction skilled trades: career progression, challenges, and motivational factors - Hannah, Richard; Parzyck, Andrew; Janzen, Andrea; Portinari, Amanda (Engaged Management ReView, 2025)
Women remain significantly underrepresented in the construction industry, particularly in the skilled trades. Through qualitative exploratory interviews with six women, this study investigates the career trajectories, worksite barriers, and motivational influences shaping women’s experiences in the construction skilled trades. The research is framed using Donald Super’s Life-Span, Life-Space theory and expectancy-value theory (EVT) to explore how career stages and career value affect women’s experiences. Participants described gender bias, limited mentorship, and restricted advancement opportunities as primary challenges. This study highlights the need for industry-led initiatives to increase early exposure to trades, improve mentorship and sponsorship programs, and create structured pathways for career advancement.
Keywords: Affect (linguistics); Career Pathways; Career development; Exploratory research; Mentorship; Qualitative research; Value (mathematics); dept.com

The Neurospicy Queer Experience: Insights Into the Lived Experiences & Counseling Needs of Transgender and Gender Expansive Adults with ADHD - Gorski, J.; Bonjo, L.; Sassu, Kari; Councilor, KC (Journal of LGBTQ Issues in Counseling, 2026)
Keywords: ADHD; Expansive; Human sexuality; Lived experience; Qualitative research; Queer; Transgender; dept.com; dept.csp; gender affirming care; gender expansive; neurodivergence; neuroqueer; neurospicy

Gendered bodies: A graphic medicine commentary - Barry Councilor, K.C.; Fink, A.E. (Social Science and Medicine, 2024)
This final commentary, in comic format, frames this special issue using Graphic Medicine methodologies to explore broader themes and meanings related to the scientific study of gender and health. Comics can be seen as a way to introduce complex human narratives and as an exploratory tool to ask broader social-contextual and ethical questions about health and medicine. This piece is also constructed through the lens of queer scholarship, which, together with the comics format, provides opportunities to build more embodied, complicated narratives about gender, sexuality and health. Most importantly, comics are used as a modality to tell compelling narratives about how individuals, rather than populations, may be impacted by biomedical conceptualizations of gender and health. The commentary includes a series of graphic narratives containing hypothetical stories and cases: stories of how individuals may be harmed within healthcare systems by rigid framings of gender, sex and sexuality, and stories about how gender socialization may impact health in subtle ways. These narratives furthermore examine the inextricable link between gender and power, illustrating how overt and covert manifestations of power may shape a person's health over the life course. Finally, the piece explores how expansive views of gender may contribute to positive health care experiences. The intention of this piece is to nudge scientific researchers and clinicians alike to approach the topic of gender, sexuality and health with nuance and curiosity. © 2023 The Author(s)
Keywords: Comics; Embodiment; Gender; Gender-affirming care; Graphic medicine; Health; Narrative; Power; Sex; Sexuality; Transgender; Trauma; dept.com; peer-reviewed

Improving Psychological and Emotional Well-Being of the First-Year College Students - Robinson, Dyan; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2021)
Almost half of the students who begin college are not retained at the institution in which they began. The purpose of this research was to explore the perceptions of first-year college students to improve their psychological and emotional well-being.  This quantitative study utilized the College Student Mentoring Scale that includes two interrelated constructs which are, Psychological and Emotional Support and The Existence of a Role Model. The research found that multiple factors impact first-year students' perceptions of their psychological and emotional well-being. Additional findings indicated that response levels were highest for The Existence of a Role Model.  It is the intention that this study will add to the somewhat limited research on improving the psychological and emotional well-being of first-year college students in higher education. Also, it will assist in future policies and practices by providing a foundation of the components that influence first-year student success through improving the effectiveness of peer mentoring programs.
Keywords: dept.com; dept.edl; dept.fye; first-year college students; peer-reviewed; ⛔ No DOI found

Exploring the influence of cultural and health beliefs on intentions to adopt COVID-19 prevention measures - Dam, L.; Basaran, A.-M.B.; Lin, C.A.; Rogers, D. (Atlantic Journal of Communication, 2022)
This study explores how individuals react to COVID-19 prevention measures in relation to their national cultural values and health belief factors. Specifically, guided by the most relevant Hofstede’s cultural dimensions and the health belief model (HBM), this study tested a conceptual framework through conducting a survey of the U.S. adult population. The study results did not support Hofstede’s classification of the U.S. to be among the most individualistic culture with the lowest level of uncertainty avoidance in the world. Demographic factors such as ethnicity, gender, age, and education were found to be significantly related to collectivistic tendency and/or uncertainty avoidance. Findings also demonstrated that the tendency for collectivism and uncertainty avoidance were both relevant to people’s intention to adopt COVID-19 prevention measures. Results of testing the HBM variables revealed that perceived barriers, perceived self-efficacy, and cues to action were significantly related to preventive behavioral intentions. This study highlights the importance of considering subculture factors when promoting COVID-19 preventive measures in a multicultural society. © 2022 Atlantic Journal of Communication.
Keywords: dept.com; peer-reviewed

The impact of mass media-delivered family planning campaigns in low- and middle-income countries: A meta-analysis of advertising and entertainment-education format effects - Rogers, Dana; Snyder, Leslie B.; Rego, Michelle M. (Studies in family planning, 2021)
Effective family planning methods are shown to save lives, contribute to gender equality, and boost economic development. Mass media communication campaigns in low- and middle-income countries have been effective in increasing contraceptive use, although the strategies that increase the likelihood of success are unclear. The present study uses meta-analyses to uncover the average effect of media campaigns on family planning behaviors in low- and middle-income countries and to examine the effectiveness of two communication strategies: entertainment-education and advertising/public service announcements. Results indicated that mass media-delivered family planning campaigns have a positive impact on family planning behaviors: d = 0.19, 95% CI [0.15, 0.24] for women (k = 64), d = 0.16, 95% CI [0.11, 0.21] for men (k = 27), and d = 0.20, 95% CI [0.17, 0.23] for an undifferentiated target group of men and women (k = 37). The use of an entertainment-education format, often in addition to campaign advertising messages, was associated with greater campaign success rates for women. Men, however, responded negatively to education-entertainment and positively to campaigns using only advertising and public service announcement formats. Recommendations for future family planning mass media campaigns and academic research opportunities are discussed. © 2021 The Population Council, Inc.
Keywords: adult; advertising; article; contraceptive use; dept.com; developing world; education; family planning; female; human; human experiment; male; mass media; mass medium; meta analysis; meta-analysis; middle income country; peer-reviewed; public service announcement; type D behavior

How the operationalization of exposure impacts studies on direct-to-consumer advertising of prescription drugs - Savelli, Melanie R. (International Journal of Pharmaceutical and Healthcare Marketing, 2020)
Purpose: Without having a shared operationalization of what constitutes a direct-to-consumer advertising (DTCA) exposure, it is impossible to accurately generalize findings about their effects. First, it needs to be established how the variables involved in exposures impact outcomes. This will allow for more accurate operationalizations. Design/methodology/approach: A sample of 216 participants were recruited from Amazon’s Mechanical Turk and randomly assigned into one of four conditions to take an online survey. A 2 × 2 experiment (active/passive attention × low/high exposure) was conducted to determine if the level of attention, otherwise known as attentiveness, and the number of exposures impacted preferences for a fictitious prescription sleep aid. Findings: Results indicated a significant difference among active and passive conditions such that active exposures resulted in stronger positive preferences. Research limitations/implications: Studies using different operationalizations should not be aggregated for generalizations about the effects of DTCA of prescription drugs. Originality/value: This paper urges researchers to clearly operationalize their definitions for “exposure” and to be hesitant about generalizing findings studies using different definitions. © 2020, Emerald Publishing Limited.
Keywords: Advertising; Direct-to-consumer; Exposure; Pharmaceutical marketing; Prescription drugs; dept.com; peer-reviewed

Mentoring, sponsorship, and gender - Burke, Karen P.; Ciccomascolo, Lori E. (Social Justice and Putting Theory Into Practice in Schools and Communities, 2020)
The lack of women in leadership roles is a systemic problem in the United States and is not unique to the field of education; however, it is important to continue to challenge the status quo and provide a path for women to achieve equality and equity in the workplace. The following chapter will identify and discuss the importance of mentoring and sponsorship so that women pursuing education careers, novice women teachers, and women college, and university faculty and staff can actively and better position themselves to move into leadership positions and/or ensure a “seat at the table” in situations where decisions are made that affect their personal and professional lives.
Keywords: dept.com